Stress echocardiography in patients with ischemic mitral regurgitation and left ventricular dysfunction qualified to cardiosurgery treatment. (4th February 2022) - Piatkowski, R; Kochanowski, J; Budnik, M; Peller, M; Grabowski, M; Opolski, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Ischemic mitral regurgitation (IMR) is predominantly related to left ventricle (LV) remodeling and mitral valve deformation. Although coronary artery bypass grafting alone (CABGa) or with mitral annuloplasty (CABGmp) is considered the best therapeutic strategies for patients with IMR, some recurrences are still reported. Purpose: The aim of this study was to evaluate use of the mitral deformation indices (MDI) as a predictor of recurrence of IMR in 1-year follow-up after surgery. Methods: A total of 145 patients after myocardial infarction with significant IMR, eligible for CABG, were prospectively enrolled in the study. Patients were referred for CABGa (gr.1; n = 90) or CABGmp (gr.2; n = 55), based on clinical assessment and the results of rest and stress echocardiography. One year after surgery each patient underwent the evaluation of cardiovascular events. Univariable logistic regression analysis was used to identify factors of recurrence of IMR in 1 year follow-up. Results: Logistic regression analysis revealed that in CABGa group preoperative changes of TA and CH during DBX remained the predictors of the recurrence of IMR in 12 months follow-up. TAdbx > 1 cm2 provided sensitivity of 90% and specificity of 29%, (AUC 0.6436); The best cut-off value for CHdbx was 0.4 cm (sensitivity 90%, specificity 34%; AUC 0.6432). In both groups no significant differences were observed in 12-month mortality (1.2% vs 0%; p = 1.0), hospitalizations due to the heart failure (HF) exacerbation (5.9% vs 8.5%; p = 0.72) and in the incidence of the composite endpoint (deaths/CV hosp/stroke) (7% vs 8.5%; p = 0.742). Conclusion: Preoperative assessment of MDI changes during dbx can be used to identify patients with IMR at increased risk of recurrence of significant IMR in 1 year follow-up.